Gulliver's Politics: Conservatives Envision Potential Enemies as Readily Vanquished and Physically Small. (August 2017) - Holbrook, Colin; López-Rodríguez, Lucía; Fessler, Daniel M. T.; Vázquez, Alexandra; Gómez, Ángel
Political conservatives have been widely documented to regard out-group members as hostile, perceive individuals of ambiguous intent as malevolent, and favor aggressive solutions to intergroup conflict. A growing literature indicates that potential violent adversaries are represented using the dimensions of envisioned physical size/strength to summarize opponents' fighting capacities relative to the self or in-group. Integrating these programs, we hypothesized that, compared to liberals, conservatives would envision an ambiguous out-group target as more likely to pose a threat, yet as vanquishable through force, and thus as less formidable. Participants from the United States (Study 1) and Spain (Study 2) assessed Syrian refugees, a group that the public widely suspects includes terrorists. As predicted, in both societies, conservatives envisioned refugees as more likely to be terrorists and as less physically formidable. As hypothesized, this "Gulliver effect" was mediated by confidence in each society's capacity to thwart terrorism via aggressive military or police measures.